Lipids and oxidative stress as mediators of endothelial pathophysiology in obesity - Donovan, Elise Laura, author; Miller, Benjamin F., advisor; Hamilton, Karyn L., advisor; Hickey, Matthew S., committee member; Frye, Melinda A., committee member (Colorado State University. Libraries, 2011)
Because obesity is a well established independent risk factor for diabetes and coronary artery disease (CAD), it is important to identify factors associated with obesity that are responsible for disease progression and interventions to decrease risk of developing obesity associated co-morbidities. Two of the many mediators of obesity associated risk for diabetes and CAD are oxidative stress and oxidized phospholipids, which have been implicated in vascular disease initiation and progression through endothelial cell activation, macrophage recruitment and advanced plaque rupture. Plasma platelet activating factor acetylhydrolase (Lp-PLA2) is an enzyme that circulates bound to LDL cholesterol and degrades platelet activating factor (PAF), a potent inducer of the platelet coagulation cascade and thrombosis. In addition, Lp-PLA2 degrades oxidized phospholipids to lysophospholipid products and fatty acids that may also induce inflammatory changes in multiple cell types, including vascular endothelial cells. Exogenous antioxidant supplementation has been examined as a means of decreasing vascular oxidative stress. However, data show that exogenous antioxidant supplementation has little or no effect on CVD outcomes, and in some cases it may increase mortality. A novel approach to protecting cells from oxidative stress is to increase cellular endogenous antioxidant defenses. NF-E2-related factor 2 (Nrf2) is a transcription factor that binds to the antioxidant response element (ARE) promoter region of many genes including phase II antioxidant enzymes. Protandim is a combination of phytochemicals that is thought to induce Nrf2 stabilization and translocation to the nucleus, with subsequent increases in phase II antioxidant enzymes and protection against oxidative stress. The overall objectives of the three studies we performed were to 1) globally analyze obesity associated lipid and oxidative stress using lipidomics techniques 2) determine the effects of identified obesity associated oxidative and lipid stress on the vascular endothelium 3) determine whether Protandim treatment could protect vascular endothelial cells from an oxidative challenge, and 4) characterize Lp-PLA2 in human adipose and skeletal muscle. Experiment 1 tested the hypothesis that oxidized phospholipids would be greater in morbidly obese gastric bypass patients compared to lean surgical controls, and that global lipid profiles would differ between groups. To test this hypothesis we performed a combined targeted and global lipidomic analysis of plasma lipids from morbidly obese gastric bypass patients and lean controls. We identified a group of ether-linked lipids that were greater in obese subjects compared to lean, and further examined whether a representative lipid from this group induced pathophysiological phenotypic changes in vascular endothelial cells. Experiment 2 tested the hypothesis that Protandim would protect human coronary artery endothelial cells (HCAEC) against an oxidative challenge by increasing phase II antioxidant enzymes in a Nrf2 dependent manner. To do this we performed a series of in vitro experiments treating HCAEC with Protandim and determined that Protandim induced Nrf2 nuclear localization, increased phase II antioxidant enzyme expression, and protected cells from undergoing apoptosis in response to an oxidative challenge. Silencing Nrf2 prior to the oxidative challenge inhibited the Protandim induced protection. Experiment 3 tested the hypothesis that Lp-PLA2 would be detectable in human adipose tissue and that Lp-PLA2 would be greater in adipose from morbidly obese gastric bypass patients compared to lean. In addition, we examined whether adipose Lp-PLA2 may be related to circulating Lp-PLA2 activity, inflammation, and glucose intolerance. We have identified ether-linked lipids that are elevated in obese subjects compared to lean. We found that Lp-PLA2 is expressed in human adipose for the first time, adipose Lp-PLA2 is co-localized with macrophages, and report relationships between Lp-PLA2 and indices of glucose homeostasis and inflammation. Lastly, we found that Protandim protects endothelial cells from an oxidative challenge in a Nrf2 dependent manner. Collectively, these data provide insight into the oxidative and lipid stress milieu that occurs in obese subjects.
Keywords: endothelial cells; lipoprotein-associated phospholipase A2; obesity; oxidative stress; oxidized phospholipids; Protandim